Education and Work in General Secondary Schools. Report of a Regional Planning Panel (Bangkok, Thailand, June 24-July 5, 1982) - United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and the Pacific; United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and the Pacific ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This report summarizes the First APEID (Asian Programme of Educational Innovation for Development) Regional Planning Panel Meeting on Work and Vocational Experiences in General Education that focused on the linking of education to the world of work. An introduction gives an overview of the panel's aims, the basic principles and concepts advocated by the panel, and the context. Chapter 2 reviews the current situation in the participating countries--Bangladesh, China, India, Indonesia, Japan, Pakistan, the Philippines, the Republic of Korea, Sri Lanka, the Socialist Republic of Viet Nam, and Thailand. Areas considered are national policies, programs, and plans; curriculum; instructional materials; physical facilities; preparation of teachers; and career guidance. Chapter 3 analyzes eight issues and growth points identified for in-depth study: (1) work ethics and work habits, (2) vocational orientation and guidance, (3) taking education to the work situation, (4) utilization of local human and material resources, (5) how to promote public acceptance, (6) applied research and summing up of experiences, (7) assessment of students' performance, and (8) provision of teachers. Future activities suggested by the panel are discussed in chapter 4, namely intercountry study visits, amplification of country reports and preparation of a directory, and case studies of national experiences. Appendixes include the opening address, agenda, and a list of participants. (YLB)
Availability: Unipub, P.O. Box 433, Murray Hill Station, New York, NY 10016.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Guidance; Education Work Relationship; Educational Planning; Foreign Countries; National Programs; Policy; Regional Planning; Secondary Education; Teacher Education; Vocational Education; Work Experience; Work Experience Programs; Asia; Bangladesh -- China -- India -- Indonesia -- Japan -- Korea -- Pakistan -- Philippines -- Sri Lanka -- Thailand -- Vietnam; Collected Works, Proceedings; Reports, Descriptive